On the Poisson transform on a homogenous vector bundle over the quaternionic hyperbolic space - Ouald Chaib, Achraf (Comptes Rendus. Mathématique)
Let $K× _M V$ be the homogenous vector bundle over $K/M=Sp(n)× Sp(1)/Sp(n-1)× Sp(1)$ associated to an irreducible representation $(δ _{ν }, V)$ of Sp(1). We give an image characterization of the Poisson transform $\mathcal{P}_{λ ,ν }$ of $L^{2}$-section of $K× _M V$. We also show that $\mathcal{P}_{λ ,ν }f$, $f$ $\in L^{p}(K× _M V) $ satisfies a Hardy-type estimate.